DIALO G UMAT BER AGAMA: DARI MOBILISASI KE PARTISIPASI AKTIF DALAM ANALISA KEINDONESIAAN - Salamet, Salamet (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2018)
Interreligious dialogue in communities can be realized well in social life and is meaningful only if it is capable of being translated into active participation. If the dialogue is only conceptually rational, the dialogue will bemerely lip service wiped out by the wind. Dialogue from mobilization into active participation must be conducted to achieve human safety, harmony and peace. As the case in Indonesia, whose society is pluralistic, multiculturaland pluralistic active participation in interreligious dialogue will be a very solution to the conflicts that have occurred in the name of religion. Indonesia-ness and diversity must also not only be conceptually rational, but must be an active movement in people’s lives through various ways and means. This paper attempts tobuild awareness that dialogue between religious groups based on active participation is very important for a pluralistic Indonesian society.Key words: Interreligious Dialogue, Mobilization, Indonesia-ness